1 Corinthians 10-16 : a handbook on the Greek text - Brookins, Timothy A.; Longenecker, Bruce W. (Waco, Texas : Baylor University Press, 1947)
Timothy Brookins and Bruce Longenecker provide a foundational analysis of the Greek text of 1 Corinthians. Distinguished by the detailed yet comprehensive attention paid to the Greek text, 1 Corinthians is a convenient pedagogical and reference tool that explains the form and syntax of the biblical text, offers guidance for deciding between competing semantic analyses, engages important text-critical debates, and addresses questions relating to the Greek text that are frequently overlooked or ignored by standard commentaries. Beyond serving as a succinct and accessible analytic key, 1 Corinthians also reflects the most recent advances in scholarship on Greek grammar and linguistics. By filling the gap between popular and technical commentaries, these handbooks become indispensable tools for anyone committed to a deep reading of the biblical text. - book blurb.
Includes bibliographical references (pages 217-227) and indexes.
Keywords: Bible. -- Criticism, Textual; Bible. -- Versions